2020
DOI: 10.1186/s12301-020-00093-y
|View full text |Cite
|
Sign up to set email alerts
|

Yolk sac tumor in intraabdominal undescended testis in a child with normal serum alpha-fetoprotein: a rare case report

Abstract: Background Intraabdominal testicular tumors are rare in prepubertal children, and most of the cases reported are intraabdominal testicular teratoma. The present study reports the first case of intraabdominal testicular yolk sac tumor (YST) with normal preoperative serum alpha-fetoprotein levels and diagnosis confirmed on histopathology and immunohistochemistry. Case Presentation A 2-year-old boy presented with bilateral nonpalpable undescended testes (UDT) and abdominal mass. Preoperative serum alpha-fetopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been suggested that alpha feto protein can be applied as a feasible tumor marker because its level is elevated in > 90% of yolk sac tumor. Testicular tumors in intraabdominal sites can present either as asymptomatic testicular mass detected during evaluation of nonpalpable undescended testis or with symptoms like abdominal pain or lump associated with nausea, vomiting, low grade fever or intraabdominal testicular tumors (4) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that alpha feto protein can be applied as a feasible tumor marker because its level is elevated in > 90% of yolk sac tumor. Testicular tumors in intraabdominal sites can present either as asymptomatic testicular mass detected during evaluation of nonpalpable undescended testis or with symptoms like abdominal pain or lump associated with nausea, vomiting, low grade fever or intraabdominal testicular tumors (4) .…”
Section: Discussionmentioning
confidence: 99%